Analysis of composite bridges with intermediate diaphragms & assessment of design guidelines. (1st July 2020) - Tsiptsis, Ioannis N.; Sapountzaki, Olga E.
Highlights: Formulation for the generalized warping and distortional analysis of composite curved beams with intermediate diaphragms. Spatial curved beams under general loading and boundary conditions. Finite Element models with shell elements for bridge decks with composite open and closed cross sections usually employed in practice. Influence of the diaphragms' plate thickness and their optimum positions. Assessment of the design guidelines which specify the maximum spacing of intermediate. Abstract: In this research effort, the generalized warping and distortional problem of straight or horizontally curved composite beams of arbitrary cross section, loading and boundary conditions is presented. An inclined plane of curvature is also considered (with respect to the horizontal plane) in order to account for a slope in the cross-section plane. Additionally, a finite stiffness of diaphragmatic plates has been introduced in the formulation in order to compare with the beam models where rigid diaphragms are considered, as usually is assumed in practice. The numerical method employed for the 1D beam formulation is based on Isogeometric tools (NURBS) while the 3D shell or solid models are developed in Finite Element commercial software for composite cross sections with diaphragms. The influence of friction on the contact interaction between the concrete and steel parts is also considered. The number of intermediate diaphragms is determined according to commonly used bridge design guidelines and the results are compared to the developed arrangements in order to assess the overall structural behavior of bridge decks. Straight or curved beam models with open or closed composite cross sections of full (1D proposed beam) or partial material-bonding (3D solid/shell models) and various arrangements of intermediate diaphragms and materials have been studied.